An abundant membrane protein in the NCAM superfamily is required for epithelial organization in sea anemone embryos - Anna Postnikova; Julissa G. Tello; Maristhela Alvarez; Grace Y. Lee; Ilhan Ali; Christine M. Field; Timothy J. Mitchison; Katerina Ragkousi (Proceedings of the National Academy of Sciences, 2025)
Assembly of cells into epithelial layers marks the early steps of tissue organization and embryonic development in most animals. Although several conserved proteins are known to be essential for epithelialization in bilaterians, it is unclear whether these are sufficient to drive epithelial organization in all metazoans. Using proteomics and knockdown approaches in embryos of the early-branching sea anemone Nematostella vectensis , we identified the Neural Cell Adhesion Molecule (NCAM) NCAM2 to be essential for organization of the primary epithelial layer. NCAM2 belongs to the Immunoglobulin superfamily of cell adhesion molecules with roles in intercellular adhesion and signaling. In this work, we show that NCAM2 is enriched at the apical cell junctions and is required for Nematostella epithelial organization. Importantly, embryos depleted for NCAM2 fail to gastrulate. Both whole-embryo germ layer patterning and epithelial integrity required for gastrulation are impaired. Our results highlight the importance of an NCAM superfamily-protein in the organization of primary epithelia and early embryonic development.